Optimization of Productive Zakat: a Catalyst for Achieving Economic Independence in Aceh - Razali, Razali; Maulana, Nora; Taufiq, Taufiq; Putra, Muhammad Deni (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2024)
The potential of zakat in Aceh occupies the 7th position as a province in Indonesia, annually reaching Rp 195.4 billion. However, it has not been able to be realised optimally so that it has not overcome poverty. In fact, Aceh still remains as the poorest province in Sumatra in recent years. This research aims to describe the prospect of productive zakat empowerment in Aceh so as to be able to offer zakat management strategies in Aceh, especially in alleviating poverty. This research is a field research with descriptive qualitative method. Primary data is taken from interviews with key informants such as employees of amil zakat institutions and religious leaders. Observation is done by observing various aspects related to productive zakat management in Aceh. The results showed that the strategy in optimising productive zakat in Aceh by conducting feasibility analysis of zakat recipients, compiling entrepreneurship education and training programs, building harmonisation with various stakeholders, developing productive infrastructure, implementing monitoring and evaluation systems, ensuring accountability and increasing productive zakat literacy. Optimisation of productive zakat in Aceh synergises between amil zakat institutions, government, and sustainable communities.